2011
DOI: 10.4067/s0718-221x2011000300010
|View full text |Cite
|
Sign up to set email alerts
|

Timber management practices and timber species used by small scale furniture workshops in Uganda

Abstract: A study was done in Kampala District, Central Uganda, to document the timber species and timber management practices used in furniture workshops. A check list was used to document the common timber species, their grades, moisture contents and related timber management practices in furniture workshops. Results showed that Albizia coriaria, Markhamia lutea and Chrysophyllum albidum were the most common species while Khaya spp, Milicia excelsa and Olea spp were the least used species in the furniture workshops. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…Although the species was reported to be highly valued as timber in another regions (Uganda for instance) due to the appreciable physical and mechanical properties of its woods [ 46 ], this was not the case in the southern Benin (Plateau of Allada). The species was generally only cut down in the case of other land use such as house building or road construction.…”
Section: Discussionmentioning
confidence: 99%
“…Although the species was reported to be highly valued as timber in another regions (Uganda for instance) due to the appreciable physical and mechanical properties of its woods [ 46 ], this was not the case in the southern Benin (Plateau of Allada). The species was generally only cut down in the case of other land use such as house building or road construction.…”
Section: Discussionmentioning
confidence: 99%
“…Zziwa et al [36] explained that in order to increase the raw material base for furniture product manufacturing, an increase in the use of LUS to supplement the supply of primary timbers need encouraged. This, according to Ssseremba et al [37], would preserve firms, keep the sector operational and prevent job losses.…”
Section: Choice Of Markets For Sale Of Furniture Productsmentioning
confidence: 99%
“…However, this study showed that only 15% of manufacturers use LUS such as Celtis spp., M. indica and A. indica for furniture production. Sseremba et al [37] found M. indica among several other secondary timbers used for furniture-making in Uganda. It was further observed that none of the respondents had ever used K. gabonensis in their operations.…”
Section: Utilization Of Lus For Furniture Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, timber trade is increasingly reliant on production from trees and forests on private lands. The most common species for timber in Uganda are Maesopsis eminii, Melicia excelsa, Albizia coriaria, Chrysophyllum albidum, Lovoa trichiliodes, Funtumia elastica, Entandophragma angolense, and Podocarpus latifolius [5][6][7]. Recently demand for timber from pine trees (Pinus caribaea, Pinus patula) is on the rise [6].…”
Section: Sources Of Timber In Ugandamentioning
confidence: 99%